Child pornography - Hiber, Amanda (At issue, 2009)
Law enforcement has made great strides in combating child pornography / Laura Bush -- Law enforcement needs to do more to stop child pornography / Ernie Allen -- Possession of child pornography is punished too harshly / Alexander Cockburn -- Possession of child pornography is punished too lightly in Canada / Julian Sher -- The PROTECT Act violates First Amendment Rights / Frederick Lane -- The PROTECT Act does not violate First Amendment Rights / Mario Diaz -- The I.T. industry is helping to combat child pornography / John Foley -- Peer-to-peer file sharing software facilitates the dissemination of child pornography / Linda Koontz -- The threat of peer-to-peer file sharing software for the dissemination of child pornography is exaggerated / Martin C. Lafferty -- Internet service providers should be mandated to retain subscriber data / Alberto Gonzales -- The risks of data retention by internet service providers outweigh the rewards / Center for Democracy & Technology -- Journalists need a First Amendment exemption to report on child pornography / Debbie Nathan -- Journalists don't need to see child pornography to report on it / Alia Malek